Hot Tearing Susceptibility of Binary Mg–Gd Alloy Castings and Influence of Grain Refinement. Issue 8 (9th May 2018) - Luo, Shifeng; Yang, Guangyu; Zou, Zhen; Ouyang, Shuxia; Xiao, Lei; Jie, Wanqi
Abstract : The hot tearing susceptibility (HTS) of binary Mg–Gd alloys is tested from 1.0 to 8.0 wt% using a constrained rod casting (CRC) mold. It is found that the curve of the HTS versus Gd content follows a typical "Λ" curve: HTS increases firstly, reaches a maximum at 1.5% Gd, and then decreases, which is in good agreement with the results predicted by Clyne‐Davies model. Microstructure observations and thermodynamic calculations show that grain structure (size and morphology), the susceptible freezing range, the volume fraction of eutectic liquid, and the amount of intermetallics (Mg5 Gd) are the main factors influencing the HTS of Mg–Gd experimental alloys. The highest HTS observed in Mg–1.5Gd alloy is attributed to its coarse columnar grains, the high freezing range, and the thin and continuous liquid film as well as the hard and brittle intermetallics precipitated along the grain boundaries. In contrast, the lowest HTS observed in Mg–8Gd alloy is mainly related to the fine equiaxed grains, which can effectively accommodate the strain during solidification, and the tear healing by eutectic liquid. Furthermore, the effect of grain refinement by Zr addition on the HTS is also studied, and the results show that grain refinement can significantly reduce the HTS. Abstract : The relationship between the HTS of binary Mg–Gd alloys and Gd content shows a typical "Λ" curve: HTS increases firstly, reaches a maximum at 1.5% Gd, and then decreases, which is in good agreement with the results predicted by Clyne‐Davies model (maximum at 1.3% Gd). Furthermore, the grain refinement caused by Zr addition can significantly reduce the HTS.